Effects of Financial Situations on Mental Health in College Students - Arnold, Karsyn; Olmstead, Morgan; Wedlock, Alyssa (Kansas State University. Dept. of Sociology, Anthropology, and Social Work, 2024)
The purpose of this study is to address and explain the relationship between anxiety and access to financial assistance on the Kansas State University Campus. The study will be conducted in a quantitative, cross-sectional method utilizing 200 participants from Kansas State. Participants will complete questionnaires asking questions regarding demographics, financial status, financial assistance, and financial anxiety, as well as completing an informed consent. Financial status will be measured through a) student credit card and student loan debt and monthly income. Financial anxiety will be measured using the Financial Anxiety Scale. We expect that those individuals who have utilized financial assistance before will have lower anxiety levels and that those individuals who have not utilized financial assistance before will have higher anxiety levels. The results of this study will help determine new methods for helping college students struggling with finances. It can help bring awareness to the link between financial assistance and financial anxiety among college students.
Kirmser Undergraduate Research Award - Group category, honorable mention
Keywords: Mental Health (from authors); College Students (from authors); Anxiety (from authors); Financial Assistance (from authors); Quantitative, Cross-Sectional Study Protocol